2020
DOI: 10.1038/s41591-020-0916-2
|View full text |Cite
|
Sign up to set email alerts
|

Real-time tracking of self-reported symptoms to predict potential COVID-19

Abstract: A total of 2,618,862 participants reported their potential symptoms of COVID-19 on a smartphone-based app. Among the 18,401 who had undergone a SARS-CoV-2 test, the proportion of participants who reported loss of smell and taste was higher in those with a positive test result (4,668 of 7,178 individuals; 65.03%) than in those with a negative test result (2,436 of 11,223 participants; 21.71%) (odds ratio = 6.74; 95% confidence interval = 6.31-7.21). A model combining symptoms to predict probable infection was a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

91
1,414
21
37

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,336 publications
(1,624 citation statements)
references
References 9 publications
91
1,414
21
37
Order By: Relevance
“…Our study's findings are consistent with those of other studies evaluating both inpatient and outpatient selfreported olfactory dysfunction. [9][10][11][12]14,15 Moein et al 11 reported very high rates of measured olfactory dysfunction (98%) on quantitative analysis of COVID-19 inpatients, but only 25% showed complete anosmia and 35% selfreported smell loss. This discrepancy between quantitative and self-reported olfactory dysfunction is thought to be related to a general unawareness or underreporting of hyposmia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study's findings are consistent with those of other studies evaluating both inpatient and outpatient selfreported olfactory dysfunction. [9][10][11][12]14,15 Moein et al 11 reported very high rates of measured olfactory dysfunction (98%) on quantitative analysis of COVID-19 inpatients, but only 25% showed complete anosmia and 35% selfreported smell loss. This discrepancy between quantitative and self-reported olfactory dysfunction is thought to be related to a general unawareness or underreporting of hyposmia.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory and gustatory dysfunction have recently been found to be associated with COVID-19 infection. [9][10][11][12] The growing number of Internet searches inquiring about loss of smell strongly correlates with the increased prevalence of COVID-19. 13 In ambulatory populations, patients who present with influenza-like symptoms and anosmia are 6 to 10 times more likely to test positive for COVID-19 infection.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several drugs are currently under study and clinical trial, for example: Remdesivir, an adenosine analog that was previously tested as a potential drug for Ebola and as anti-viral drug(54), showed promising result in COVID19 patients and thus was granted an FDA Emergency Use Authorization on 1 May 2020 (55). Interestingly, taste and smell loss, (56) including impairment of the bitter taste, are reported by many COVID19 patients (57). We applied BitterIntense to possible COVID19 drug candidates and compared it to the general abundance of pVB drugs in DrugBank.…”
Section: Relationship Between Bitterness Intensity and Toxicitymentioning
confidence: 99%